An Analysis of the challenges affecting corporate governance in State Owned Enterprises(SOEs) in Kenya - Rori, Andrew Moirore (KDI School, 2011)
Efforts to improve corporate governance in the public and private sectors are gaining growing support from both outside and inside Kenya. The rationale of the study was to identify the corporate governance challenges facing state owned enterprises and how they are meeting them through various policy options, existing or new. The study was carried out at the National Social Security Fund of Kenya. The study‘s specific objectives were to establish if state owned enterprises in Kenya are subject to a binding legal system, identify the main corporate governance challenges facing state owned enterprises in Kenya and also to find out structural reforms being made by state owned enterprises in Kenya to effectively abide by the principles of corporate governance. The study was through a descriptive survey. This approach was preferred because it was considered to be most convenient and one that could ensure that the data obtained gave response to the research study questions. The research targeted 1800 employees of the National Social Security Fund. Stratified random sampling was adopted for this study. The study grouped the target population into relatively homogeneous subgroups then random sampling was applied within each stratum. A convenient and manageable sample size of 120 was identified for the study. The sample size took into consideration the study‘s sampling design. The study found out that although corporate governance is important in the management of state owned enterprises it faces several challenges among them being inadequate management and audit and assessment committee oversight of business lines, quite a number of members of the board of directors do not understand the legal, reputational, and compliance risks facing their organization. The study concluded that effective corporate governance in state owned enterprises is affected and depends on whether the state owned enterprise has clearly defined roles for directors and management, board members who are appointed based on considerations of merit and the necessary skills, qualifications and experience for the position. The study recommends that there should be separation of management functions from ownership interests, clear guidelines when procuring goods and services, proper succession plans, promotion of transparency, internal controls and the management of state owned enterprises should strive to always act responsibly.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: SOE (State Owned Enterprises)